Circular RNA circFOXO3 promotes prostate cancer progression through sponging miR‐29a‐3p - Kong, Zhe (John Wiley and Sons Inc., 2019)

(untitled) (J Cell Mol Med)
Circular RNA FOXO3 (CircFOXO3, also termed as Hsa_circ_0006404) is derived from exon 2 of forkhead box O3 (FOXO3) gene, and abnormal expression is shown in different diseases. However, whether circFOXO3 plays important roles in tumorigenesis and progression of prostate cancer (PCa) remains unclear. In this study, we found that circFOXO3 was up‐regulated in both PCa tissues and serum samples. Moreover, circFOXO3 was positively correlated with the Gleason score in PCa samples. CircFOXO3 was observed to be up‐regulated in Gleason score > 6 PCa samples compared with Gleason score = 6 PCa samples. Knock‐down circFOXO3 could remarkably inhibit PCa cell cycle, proliferation and promote cell apoptosis in vitro. Furthermore, we demonstrated circFOXO3 could act as miR‐29a‐3p sponge to up‐regulate SLC25A15 expression by bioinformatics analysis, dual‐luciferase reporter assays and biotinylated RNA pull‐down assays. SLC25A15 could reverse the tumour suppressing roles of knock‐down circFOXO3 in PCa. Of note, we found that miR‐29a‐3p was down‐regulated; however, SLC25A15 was overexpressed in PCa samples compared with normal tissues. In conclusion, circFOXO3 acts as a miR‐29a‐3p sponge to exhibit oncogenic activity that affects the cell cycle and cell apoptosis in PCa through transcriptional up‐regulation of SLC25A15. Our analysis suggests circFOXO3 could act as promising prostate cancer biomarkers.